Experimental study on flexural strength and effective elastic modulus of granular ice in the Bohai Sea, China - Xiu, Yuanren; Li, Zhijun; Wang, Qingkai; Han, Hongwei; Zong, Zhi; Zu, Yongheng; Zhang, Yaodan (Frontiers in Energy Research, 2022)
In the ice-infested Bohai Sea, ice-breaking cones are generally installed on offshore wind turbine towers for ice resistance. Bending failure is a frequent ice failure mode occurring when ice interacts with ice-breaking cones. Global warming prolongs the ice formation period in the Bohai Sea, inducing an increasing trend of granular ice fraction in ice sheets. To better understand the bending mechanical behaviors of granular sea ice in the Bohai Sea, laboratory three-point bending tests were conducted using granular sea ice collected in the Bohai Sea during the winter of 2010–2011. A total of 42 ice samples were tested at −5, −10, and −15°C with strain rates of 1×10−6–6×10−4 s−1 in the downward direction vertical to the original ice surface. During tests, the salinity and density of each ice specimen were measured to calculate the porosity. Based on the results, negative exponential relationships were proposed between flexural strength and the square root of porosity and between effective elastic modulus and porosity. After normalization, the flexural strength showed no rate dependence at the whole strain rate range. In contrast, the effective elastic modulus increased with the strain rate. The effective elastic modulus of the ice samples was further parameterized based on the porosity and strain rate.